Peningkatan Literasi Kader dan Masyarakat Melalui Pelatihan Pembuatan Konten Edukasi Kesehatan Tentang Imunisasi - Inanda, Grace Zecharrias; Nabila, Resha Rizqy; Sitepu, Abira Ivanca Eka Dewi; Priyanti, Annisa Delillah; Agustini, Rina Tri (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Immunization is an effort to increase a person's immunity against a disease. One of the things that influence someone to immunize is knowledge about immunization itself. This community empowerment aims to improve the knowledge and skills of cadres through making educational videos on health content related to immunization. Posyandu Anggrek Hitam is one of the posyandu located in Loa Bakung Village which has low immunization coverage. The method used in community empowerment is with education related to immunization and health promotion media. Then continued with training on scripting and video making of health content related to immunization. The results of this empowerment found that there was an increase in knowledge about immunization and health promotion media, as well as an increase in cadre skills related to script making and video content through making educational videos of health content related to immunization. After the community empowerment of these cadres, it is hoped that in the future cadres can be more operational in organizing posyandu in health promotion efforts using media for the community.